The development of the würde + infinitive construction in Early Modern German (1650–1800) - Durrell, Martin; Whitt, Richard J. (de Gruyter, 2016)
This paper presents a corpus-based analysis of the evolution of the würde + infinitive construction in German during the Early Modern period (1650– 1800), using newly available data from the GerManC-corpus. We demonstrate how this construction occupies a unique position orthogonal to both the tense and mood systems of German through an analysis of the syntax and semantics of würde + infinitive clauses, beginning with Modern Standard German and then subsequently with a historical focus on the late seventeenth and eighteenth centuries. Through both quantitative and qualitative analyses, we examine the contexts in which the construction occurs and see how, as it came to be used more frequently over the period in question, it encroached more and more into contexts which had been the preserve of the synthetic preterite subjunctive, even being used in some where the latter is still the norm in modern German. Thus, by the end of the eighteenth century it had become difficult to identify a clear difference in meaning and use between these forms, and the reasons why the würde + in- finitive construction may be preferred over the synthetic preterite subjunctive are by no means clear. We conclude our discussion with an overview of how the würde + infinitive construction was received in the prescriptive tradition during this key period in the standardization of German, seeing its stigmatization in some contexts in part as an attempt by prescriptive grammarians to establish an explicit and clearly justified role for it in the language.